4, 3, 2, 1: Part 2

Calculus Level 4

n = 1 n 2 4 3 n n ! = e a b \large \sum _{ n=1 }^{ \infty }{ \dfrac { { n }^{ 2 } }{ 4\cdot { 3 }^{ n }\cdot n! } } =\dfrac { \sqrt [ a ]{ e } }{ b }

If the equation above holds true for positive integers , find a + b a+b .

Clarification : e 2.71828 e \approx 2.71828 denotes the Euler's number .


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rishabh Jain
Jul 5, 2016

Write the sum as:

1 4 n = 1 ( n 2 n ) + n 3 n n ! \displaystyle\large \dfrac 14\sum _{ n=1 }^{ \infty }{ \dfrac { ({ n }^{ 2 } -n)+n}{ { 3 }^{ n }\cdot n! } }

= 1 4 ( n = 1 n ( n 1 ) 3 n n ! + n = 1 n 3 n n ! ) =\dfrac 14\left(\displaystyle\sum _{ n=1 }^{ \infty }{ \dfrac { n(n-1)}{ { 3 }^{ n }\cdot n! } }+\displaystyle\sum _{ n=1 }^{ \infty }{ \dfrac { n}{ { 3 }^{ n }\cdot n! } }\right)

= 1 4 ( n = 2 1 3 n ( n 2 ) ! + n = 1 1 3 n ( n 1 ) ! ) =\dfrac 14\left(\displaystyle\sum _{ n=2 }^{ \infty }{ \dfrac { 1}{ { 3 }^{ n }\cdot ( n-2)! } }+\displaystyle\sum _{ n=1 }^{ \infty }{ \dfrac { 1}{ { 3 }^{ n }\cdot (n-1)! } }\right)

= 1 4 ( 1 9 n = 2 ( 1 3 ) n 2 ( n 2 ) ! + 1 3 n = 1 ( 1 3 ) n 1 ( n 1 ) ! ) =\dfrac 14\left(\dfrac 19\displaystyle\sum _{ n=2 }^{ \infty }{ \dfrac { \left(\frac 13\right)^{n-2}}{ ( n-2)! } }+\dfrac 13\displaystyle\sum _{ n=1 }^{ \infty }{ \dfrac { \left(\frac 13\right)^{n-1}}{ (n-1)! } }\right)

= 1 4 ( 1 9 e 1 / 3 + 1 3 e 1 / 3 ) ( e x = r = 0 x r r ! ) =\dfrac 14\left(\dfrac 19e^{1/3}+\dfrac 13e^{1/3}\right)~~\left(\small{\because \color{#3D99F6}{e^x=\displaystyle\sum_{r=0}^{\infty}\dfrac{x^r}{r!}}}\right)

= e 1 / 3 9 \large =\dfrac{e^{1/3}}{9}

9 + 3 = 12 \Large \therefore 9+3=\boxed{\color{#D61F06}{12}} \huge\color{grey}{\star}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...